1991
DOI: 10.1007/bf02863079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an acute zinc depletion on rat lipoprotein distribution and peroxidation

Abstract: The aim of this study was to determine the extent to which zinc depletion leads to lipoprotein modifications by measuring both lipoprotein-fraction distribution and peroxidation in zinc-depleted rats. The animals were divided into three groups and fed for 8 wk a zinc-adequate diet (100 ppm) ad libitum (AL), a zinc-deficient diet (0.2 ppm) ad libitum (ZD), or a zinc-adequate diet according to the pair feeding method (PF). Trace-element status, tissular lipids, and lipoprotein-fraction study were performed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 30 publications
1
20
1
Order By: Relevance
“…The polyphenolic structures of flavonoids partition into the hydrophobic core of the membrane can cause a modulation of lipid fluidity (Arti et al, 2000). Flavonoids have been reported to inhibit peroxidation of polyunsaturated fatty acids in cell membranes (Faure et al, 1990). These substances, could react with the deeper membrane domains and intracellular structures, and protect the cells from oxidant injury (Kaviarasan et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The polyphenolic structures of flavonoids partition into the hydrophobic core of the membrane can cause a modulation of lipid fluidity (Arti et al, 2000). Flavonoids have been reported to inhibit peroxidation of polyunsaturated fatty acids in cell membranes (Faure et al, 1990). These substances, could react with the deeper membrane domains and intracellular structures, and protect the cells from oxidant injury (Kaviarasan et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Previous study on this plant revealed the presence of flavonoids, proanthocyanidins, tannins, phenols and flavonols in this plant. These compounds have been reported to possess strong antioxidant capacity [7] , therefore, could inhibit peroxidation of polyunsaturated fatty acids in the cell membrane and haemolysis of red blood cells in the diabetic animals reported by Torell and Faure et al [22,23] .…”
Section: Discussionmentioning
confidence: 97%
“…9 -11 Dietary zinc supplementation in cholesterol-fed rabbits decreases the extent of lesion lipid oxidation and attenuates atherosclerotic burden, despite insignificant changes in lesion zinc. 19 -21 Zinc deficiency in rats has been reported to enhance LDL oxidation in vitro 36 and in LDL-receptor deficient mice to result in increases in plasma lipids and induction of proinflammatory events. 37 However, zinc supplementation of apoE-deficient mice on a high-fat high-cholesterol diet did not confer protection.…”
Section: Discussionmentioning
confidence: 99%